N10 Facilitators and inhibitors to first adult care visits in the transition from paediatric to adult orientated Inflammatory Bowel Disease healthcare. (30th January 2023) - Rea, J; Greaney, A M; Farrell, D
Abstract: Background: Inflammatory bowel disease (IBD) can be a very debilitating disease and it is found to be more extensive in children with rapid early progression. The successful transition of patients from paediatric to adult-oriented services is essential to prevent disruption in care and negative effects on long-term health outcomes. In particular, the attendance at the first adult care visits are a pivotal phase of a successful transition process to ensure continuity and retention in care. The aim of this study is to explore the inhibitors and facilitators to first adult care visits in the transition process from paediatric to adult oriented IBD healthcare. Methods: An exploratory, descriptive, qualitative approach was employed, underpinned by a transition theory (Meleis, 2010). A purposive sample of seven participants (over 16 years of age) diagnosed with IBD, who transitioned in the last four years, were recruited, through two clinical sites in Ireland, and an IBD support organisation. Online semi-structured interviews were conducted via Microsoft Teams and data were analysed using content analysis. Results: Three main themes were identified including the ' perception of transition', 'knowledge and preparation' and ' being an adolescent with IBD' . The themes illuminate various inhibitors and facilitators to the first adult care visits. The theme perception of transition revealed that joint care visits and adult healthcare teams that actively engage with adolescents during the first adult care visits were facilitators, whereas difficulties contacting the adult services, lack of effective follow up and the change in language were inhibitors. More than one joint visit with the adult and paediatric healthcare teams and active promotion of independence facilitated knowledge and preparation for the first adult care visits. In contrast, a limited focus on disease management education and significant parental involvement inhibited the development of knowledge and preparation for the first adult care visits. Addressing adolescent specific topics, such as sexual health, and the availability of IBD supports, such as an IBD psychologist, social media platforms and meeting peers with IBD, supported being an adolescent with IBD and facilitated the first adult care visits. Conclusion: Multiple, organised joint care visits with an active focus on promoting independence and providing education on disease management and adolescent specific topics, using age appropriate language, facilitates first adult care visits. Identifying the inhibitors and facilitators provide insights for healthcare professionals in supporting a successful transition process and highlights the need for transition policies and structured transition programmes.